Preparation method of nitrogenous supercapacitor carbonaceous electrode material
By doping nitrogen atoms and adopting specific carbonization treatment methods, carbonaceous electrode materials for nitrogen-containing supercapacitors were prepared, which solved the problems of low energy density and power density of existing electrode materials and achieved higher electrochemical performance.
Patent Information
- Application Number
- CN202411567178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The existing carbonaceous electrode materials have low energy density and power density, making it difficult to meet the needs of higher performance supercapacitors.
By doping nitrogen atoms, a carbonaceous electrode material of nitrogen-containing supercapacitor is prepared by mixing and carbonizing the carbon-rich precursor with KOH powder, and then further carbonization is performed under a nitrogen atmosphere to increase the specific surface area of the electrode material and pore size distribution.
The energy density, power density and specific capacitance of the electrode material are improved, and the electron-supplying characteristics of the carbon matrix and the wettability of the activated carbon surface are enhanced.
Smart Images

Figure CN119409190A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitor electrode materials and relates to a method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material. Background Art
[0002] Supercapacitors are a new type of energy storage device between traditional capacitors and batteries. They have become a research hotspot in the field of new energy due to their excellent characteristics such as fast charging and discharging speed, long cycle life, high energy density and no pollution. Their application in hybrid vehicles, solar energy, wind energy, etc. is expected to have a fundamental impact on energy conservation and urban environmental control. The core part of supercapacitors is electrode materials, and the performance of electrode materials directly affects the performance of supercapacitors.
[0003] The electrode materials that are being studied most are carbon porous materials such as super activated carbon, carbon aerogel, and carbon nanotubes based on the double-layer theory. Although in theory the double-layer capacitance is proportional to the effective specific surface area of the material, the increase in the effective specific surface area must take into account the constraints on electrode performance such as the pore structure, resistivity, and density of the material, so there is a limit to the double-layer specific capacitance (C). Recently, researchers have improved the energy and power density of capacitors by directional control of the specific surface area, pore size distribution, and conductive network of carbon porous electrode materials. However, the room for improvement using this method is very limited, resulting in a low energy density E (E∝C·U 2 ) is only 10Wh / kg at most. Therefore, the preparation of carbonaceous electrode materials with higher energy density and specific power is extremely important.
[0004] Based on this, the present invention develops and prepares an electrode material by doping nitrogen atoms. The doped nitrogen atoms can provide additional pseudocapacitance for the capacitor carbon, increase the wettability of the porous carbon to the electrolyte, and thus improve the energy, power density and specific capacitance of the capacitor. Summary of the invention
[0005] In view of the above technical problems, the present invention aims to provide a method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material, comprising mixing a carbon-rich precursor with KOH powder and carbonizing to prepare activated carbon, adding the prepared activated carbon to an aqueous urea solution or a melamine-ethanol solution for immersion, drying and then carbonizing the mixture under a nitrogen atmosphere to obtain a nitrogen-containing supercapacitor carbonaceous electrode material. The preparation method of the present invention is simple, the process is easy to control, and it is suitable for large-scale production. The surface and bulk of the prepared carbonaceous electrode material are rich in nitrogen, which can enhance the electron-donating properties of the carbon matrix, improve the wettability of the activated carbon surface and produce a pseudocapacitance effect, thereby improving the energy density, power density and specific capacitance of the electrode material.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a nitrogen-containing supercapacitor carbon electrode material is carried out in the following steps in sequence:
[0008] (1) A carbon-rich precursor with a particle size of 300-400 mesh is mixed with KOH powder and placed in an activation kettle for carbonization under a nitrogen atmosphere. After cooling, the mixture is taken out and soaked in 5M HCl, and repeatedly washed with deionized water and filtered until neutral to remove residual metal K and its compounds. The activated carbon is obtained after drying at 110°C;
[0009] (2) adding the activated carbon obtained in step (1) to a urea aqueous solution or a melamine-ethanol solution, impregnating the mixture at room temperature, drying the mixture at 110° C., placing the mixture in a carbonization furnace, carbonizing the mixture under a nitrogen atmosphere for 1 to 3 hours, and cooling the mixture to obtain a nitrogen-containing supercapacitor carbonaceous electrode material.
[0010] As a limitation of the present invention, in step (1), the carbon-rich precursor is one or more biomass materials such as coal, petroleum coke, asphalt coke, or coconut shell.
[0011] As another limitation of the present invention, in step (1), the mass ratio of the carbon-rich precursor to the KOH powder is 1:(1-4).
[0012] As a third limitation of the present invention, in step (1), the carbonization is carried out in the following order:
[0013] (a) In the first heating stage, the temperature is raised from room temperature to 100-250°C at a heating rate of 5-10°C / min and kept at this temperature for 0.5-3h;
[0014] (b) the second heating stage, heating from 100 to 250°C to 300 to 500°C at a heating rate of 5 to 10°C / min, and keeping the temperature for 0.5 to 3h;
[0015] (c) The third heating stage: the temperature is increased from 300-500°C to 700-1000°C at a heating rate of 5-10°C / min and kept at this temperature for 0.5-3h.
[0016] (d) Cooling stage: cooling to room temperature along with the furnace.
[0017] As is known to all, the carbonization process of preparing activated carbon will have a great influence on the pore size of the activated carbon, thereby affecting the specific surface area and adsorption performance of the activated carbon, and further affecting the performance of the electrode material. In the first heating stage of the present invention, the temperature is increased from room temperature to 100-250°C at a heating rate of 5-10°C / min, and physical dehydration is performed at 100-250°C. In this stage, if the heating rate is too fast or the temperature is less than 100°C, insufficient dehydration will result. If the heating rate is too slow, energy consumption will increase. If the temperature is greater than 250°C, violent boiling will occur. Keeping warm for 0.5-3h is beneficial to the dehydration of the carbon precursor. In the second heating stage, the temperature is increased from 100-250°C to 300-500°C at a heating rate of 5-10°C / min, and chemical dehydration is performed at 300-500°C. In this stage, if the heating rate is too fast or the temperature is less than 100°C, insufficient dehydration will result. If the heating rate is too slow, energy consumption will increase. If the temperature is greater than 250°C, violent boiling will result. Keeping warm for 0.5-3h is beneficial to the dehydration of the carbon precursor. If the heating rate is too fast or the temperature is less than 300℃, a large amount of water will be produced in the next activation process, which will cause the material to stick to the wall. If the heating rate is too slow, energy consumption will increase. If the temperature is greater than 500℃, the activation and pore-making step will be entered in advance, which will cause the material to stick to the wall. Keeping warm for 0.5 to 3 hours is conducive to sufficient dehydration of KOH. In the third heating stage, the temperature is increased from 300 to 500℃ to 700 to 1000℃ at a heating rate of 5 to 10℃ / min, and activation and pore-making are carried out at 700 to 1000℃. If the heating rate is too fast or too slow at this stage, the pore size distribution of the activated carbon will be affected. If the temperature at this stage is greater than 1000℃, the activation will be excessive and the specific surface area of the activated carbon will be reduced. If the temperature is less than 700℃, the activation will be insufficient, thereby reducing the specific surface area of the activated carbon. Keeping warm for 0.5 to 3 hours is conducive to sufficient activation.
[0018] As a fourth limitation of the present invention, in step (2), the mass ratio of urea to water in the urea aqueous solution is 1:(1-5).
[0019] As a fifth limitation of the present invention, in step (2), the mass ratio of melamine to ethanol in the melamine-ethanol solution is 1:(2-8); and the ethanol is an ethanol aqueous solution with a volume concentration of 80%.
[0020] As a sixth limitation of the present invention, in step (2), the mass ratio of the activated carbon to the urea aqueous solution or the melamine-ethanol solution is 1:(1-10).
[0021] As a seventh limitation of the present invention, in step (2), the immersion time is 5 to 24 hours.
[0022] As the last limitation of the present invention, in step (2), the carbonization temperature is 400-1000° C., and the heating rate is 5-10° C. / min.
[0023] As we all know, the performance of electrode materials directly affects the performance of supercapacitors, and the carbonization process of electrode materials has a great influence on the performance of electrode materials. If the carbonization temperature is less than 400°C, it will affect the storage form of nitrogen; if the carbonization temperature is greater than 1000°C, some pores will collapse, reducing the specific surface area; when the heating rate is greater than 10°C / min, it will affect the effective combination of nitrogen and carbon, and when the heating rate is less than 5°C / min, it will increase energy consumption.
[0024] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0025] The above technical solution has the following advantages or beneficial effects:
[0026] 1. The present invention adopts urea or melamine as a nitrogen source, and through high-temperature reforming combined technology, the prepared carbonaceous electrode material has a moderate nitrogen content, a large specific surface area and a reasonable pore size distribution, and good electrolyte wettability. Its mass energy density, volume energy density, and specific power are all higher than those of existing carbonaceous electrode materials.
[0027] 2. The present invention controls the carbonization temperature to promote the reformation of nitrogen-containing functional groups loaded on the surface of activated carbon, so that nitrogen atoms are directly bonded to the skeleton of the carbon matrix, and the nitrogen loading is made more uniform through liquid phase loading.
[0028] 3. The preparation process used in the present invention is simple, the raw materials are widely available and the price is low.
[0029] The invention is suitable for preparing carbonaceous electrode materials for nitrogen supercapacitors.
[0030] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XPS spectrum (N1s) of the nitrogen-containing supercapacitor carbon electrode material prepared in Example 1 of the present invention;
[0032] Figure 2 This is the XPS spectrum (N1s) of the nitrogen-containing supercapacitor carbon electrode material prepared in Example 2 of the present invention;
[0033] Figure 3 This is a pore size distribution diagram of the nitrogen-containing supercapacitor carbonaceous electrode material prepared in Example 1 and Example 2 of the present invention and the activated carbon before nitrogen loading. DETAILED DESCRIPTION
[0034] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0035] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0036] Example
[0037] Example 1
[0038] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0039] (1) Coal powder with a particle size of 300-400 mesh and KOH powder were mixed uniformly in a mass ratio of 1:4. Under nitrogen protection, the mixture was heated to 100°C at a heating rate of 5°C / min for low-temperature physical dehydration for 1 h, and then heated to 400°C at the same heating rate for chemical dehydration for 1.5 h. The mixture was further heated to 800°C at the same heating rate and activated for 1 h. The mixture was naturally cooled to room temperature and then taken out, soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0040] (2) The activated carbon obtained in step (1) and the urea aqueous solution (the mass ratio of urea to water is 1:1) are mixed in a mass ratio of 1:7 and immersed at room temperature for 24 hours. After filtering, they are dried at 110°C and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature is increased to 900°C at a heating rate of 5°C / min and carbonized for 2 hours. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material is obtained.
[0041] The electrode material prepared in Example 1 was tested and its BET specific surface area was 3200 m 2 / g, the pore size is concentrated in the range of 0.5 to 5.0 nm, such as Figure 3 As shown in the figure, the specific surface area and pore size distribution of the carbonaceous electrode material after nitrogen loading did not change significantly compared with the activated carbon before nitrogen loading, which shows that the large specific surface area and pore size distribution of the original activated carbon can be retained while loading nitrogen. The types and contents of nitrogen-containing functional groups in the prepared electrode material are shown in the figure. Figure 1 , as shown in Table 1. When 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 310F / g; when 1M tetraethylammonium tetrafluoroborate is used as the electrolyte, the specific capacitance of the electrode material is 170F / g.
[0042] Example 2
[0043] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0044] (1) Coal powder with a particle size of 300-400 mesh and KOH powder were mixed uniformly in a mass ratio of 1:4. Under nitrogen protection, the temperature was first raised to 100°C at a heating rate of 8°C / min for low-temperature physical dehydration for 1 hour, and then the temperature was raised to 400°C at the same heating rate for chemical dehydration for 1.5 hours. The temperature was further raised to 800°C at the same heating rate and then activated for 1 hour. After naturally cooling to room temperature, the mixture was taken out and soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0045] (2) The activated carbon obtained in step (1) is mixed with a melamine-ethanol solution (the mass ratio of melamine to ethanol is 1:2, and ethanol is an ethanol aqueous solution with a volume concentration of 80%) in a mass ratio of 1:1 and immersed at room temperature for 10 hours. After filtering, it is dried at 110°C and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature is increased to 400°C at a heating rate of 7°C / min and carbonized for 1 hour. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material is obtained.
[0046] The electrode material prepared in Example 2 was tested and its BET specific surface area was 3189 m 2 / g, the pore size is concentrated in the range of 0.5 to 5.0 nm, such as Figure 3 As shown in the figure, the specific surface area and pore size distribution of the carbonaceous electrode material after nitrogen loading did not change significantly compared with the activated carbon before nitrogen loading, which shows that the large specific surface area and pore size distribution of the original activated carbon can be retained while loading nitrogen. The types and contents of nitrogen-containing functional groups in the prepared electrode material are shown in the figure. Figure 2 , as shown in Table 1. When 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 324F / g; when 1M tetraethylammonium tetrafluoroborate is used as the electrolyte, the specific capacitance of the electrode material is 156F / g.
[0047] Example 3
[0048] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0049] (1) Petroleum coke powder with a particle size of 300-400 mesh and KOH powder were uniformly mixed in a mass ratio of 1:2. Under nitrogen protection, the mixture was heated to 250°C at a heating rate of 10°C / min for low-temperature physical dehydration for 3 h, and then heated to 500°C at the same heating rate for chemical dehydration for 3 h. The mixture was further heated to 1000°C at the same heating rate and activated for 3 h. The mixture was naturally cooled to room temperature and then taken out, soaked in 5M HCl, repeatedly washed with deionized water, and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0050] (2) The activated carbon obtained in step (1) was mixed with a urea aqueous solution (the mass ratio of urea to water was 1:3) at a mass ratio of 1:10 and immersed at room temperature for 5 h. After filtering, it was dried at 110 ° C. and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature was increased to 1000 ° C. at a heating rate of 10 ° C. / min and carbonized for 3 h. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material was obtained.
[0051] The electrode material prepared in Example 3 was tested and its BET specific surface area was 2583 m 2 / g, and the pore size is concentrated in the range of 0.5-4nm; when 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 298F / g.
[0052] Example 4
[0053] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0054] (1) Asphalt coke powder with a particle size of 300-400 mesh and KOH powder were mixed uniformly in a mass ratio of 1:1. Under nitrogen protection, the mixture was heated to 150°C at a heating rate of 10°C / min for low-temperature physical dehydration for 0.5 h, then heated to 300°C at the same heating rate for chemical dehydration for 0.5 h, and then heated to 700°C at the same heating rate for activation for 0.5 h. After naturally cooling to room temperature, the mixture was taken out, soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0055] (2) The activated carbon obtained in step (1) and the urea aqueous solution (the mass ratio of urea to water is 1:5) are mixed in a mass ratio of 1:7 and immersed at room temperature for 5 hours. After filtering, they are dried at 110°C and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature is increased to 900°C at a heating rate of 5°C / min and carbonized for 2 hours. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material is obtained.
[0056] The electrode material prepared in Example 4 was tested and its BET specific surface area was 1314 m 2 / g, and the pore size distribution is 0.5-6.0nm; when 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 302F / g.
[0057] Example 5
[0058] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0059] (1) Coal powder with a particle size of 300-400 mesh and KOH powder were mixed uniformly in a mass ratio of 1:1. Under nitrogen protection, the mixture was heated to 150°C at a heating rate of 5°C / min for low-temperature physical dehydration for 0.5 h, then heated to 300°C at the same heating rate for chemical dehydration for 0.5 h, and then heated to 700°C at the same heating rate for activation for 0.5 h. After naturally cooling to room temperature, the mixture was taken out, soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0060] (2) The activated carbon obtained in step (1) is mixed with a melamine-ethanol solution (the mass ratio of melamine to ethanol is 1:4, and ethanol is an ethanol aqueous solution with a volume concentration of 80%) in a mass ratio of 1:1 and immersed at room temperature for 10 hours. After filtering, it is dried at 110°C and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature is increased to 400°C at a heating rate of 7°C / min and carbonized for 2 hours. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material is obtained.
[0061] The electrode material prepared in Example 5 was tested and its BET specific surface area was 1356 m 2 / g, and the pore size is concentrated in the range of 0.5-3.0nm; when 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 309F / g.
[0062] Example 6
[0063] This embodiment prepares a nitrogen-containing supercapacitor carbonaceous electrode material, and the preparation process and steps are as follows:
[0064] (1) Coal powder with a particle size of 300-400 mesh and KOH powder were mixed uniformly in a mass ratio of 1:1. Under nitrogen protection, the mixture was heated to 150°C at a heating rate of 5°C / min for low-temperature physical dehydration for 0.5 h, then heated to 300°C at the same heating rate for chemical dehydration for 1.5 h, and then heated to 700°C at the same heating rate for activation for 0.5 h. After naturally cooling to room temperature, the mixture was taken out, soaked in 5M HCl, and repeatedly washed with deionized water and filtered to neutrality to remove residual metal K and its compounds. After drying at 110°C, activated carbon with ultra-high specific surface area was obtained.
[0065] (2) The activated carbon obtained in step (1) is mixed with a melamine-ethanol solution (the mass ratio of melamine to ethanol is 1:8, and ethanol is an ethanol aqueous solution with a volume concentration of 80%) in a mass ratio of 1:1 and immersed at room temperature for 10 hours. After filtering, it is dried at 110°C and placed in a carbonization furnace. In a nitrogen atmosphere, the temperature is increased to 400°C at a heating rate of 7°C / min and carbonized for 2 hours. After cooling, a nitrogen-containing supercapacitor carbonaceous electrode material is obtained.
[0066] The electrode material prepared in Example 6 was tested and its BET specific surface area was 1342 m 2 / g, and the pore size is concentrated in the range of 0.5 to 3 nm. When 3M KOH is used as the electrolyte, the specific capacitance of the electrode material is 298F / g.
[0067] The types of nitrogen-containing functional groups of the electrode materials prepared in Examples 1 to 6 were analyzed. The analysis results are shown in Table 1.
[0068] Table 1 Types and contents of nitrogen-containing functional groups of electrode materials prepared in Examples 1 to 6
[0069]
[0070] The energy density and power density of Examples 1 to 6 were tested at a current density of 0.5 A / g. The test results are shown in the following table:
[0071] Group Energy density (Wh / Kg) Power density (W / Kg) Example 1 12.0 100.2 Example 2 12.4 112.0 Example 3 10.2 98.9 Example 4 9.8 96.3 Example 5 9.5 94.8 Example 6 9.6 95.2
[0072] Comparative Example
[0073] In order to explore the influence of different parameters in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were carried out. Different nitrogen-containing carbonaceous electrode materials for supercapacitors were prepared in the following comparative examples, as follows:
[0074] Comparative Example 1
[0075] This comparative example prepares a nitrogen-containing supercapacitor carbon electrode material similar to that of Example 1, except that in step (1), the carbonization process is not subjected to stage-by-stage heating, but is directly heated to 800° C. at a heating rate of 5° C. / min and activated for 1 h.
[0076] Comparative Example 2
[0077] This comparative example prepares a nitrogen-containing supercapacitor carbonaceous electrode material similar to that of Example 1, except that in step (1), the mass ratio of coal powder to KOH powder is 1:5, and the other conditions are the same as those of Example 1.
[0078] Comparative Example 3
[0079] This comparative example prepares a nitrogen-containing supercapacitor carbonaceous electrode material similar to that of Example 1, except that in step (2), the urea solution is replaced with polyacrylamide.
[0080] Comparative Example 4
[0081] This comparative example prepares a nitrogen-containing supercapacitor carbonaceous electrode material similar to that of Example 1, except that in step (2), the mass ratio of activated carbon to urea aqueous solution is 1:11.
[0082] Comparative Example 5
[0083] This comparative example prepares a nitrogen-containing supercapacitor carbon electrode material similar to that of Example 1, except that in step (2), the carbonization process is heated to 300° C. at a heating rate of 5° C. / min and the activation treatment is performed for 3 h.
[0084] When 3M KOH was used as the electrolyte, the specific capacitance of the electrode materials prepared in Comparative Examples 1 to 5 was tested; and at a current density of 0.5 A / g, the energy density and power density of the electrode materials prepared in Comparative Examples 1 to 5 were tested, and the specific data are shown in the following table:
[0085] Comparative Example Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Specific capacitance (F / g) 273.4 278.5 256.2 275.6 276.3 Energy density (Wh / Kg) 8.6 8.5 8.1 8.4 8.4 Power density (W / Kg) 88.9 86.2 82.3 83.6 83.7
[0086] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material, characterized in that: Follow the steps below in order: (1) A carbon-rich precursor with a particle size of 300-400 mesh is mixed with KOH powder and placed in an activation kettle for carbonization under a nitrogen atmosphere. After cooling, the mixture is taken out and soaked in 5M HCl, and repeatedly washed with deionized water and filtered until neutral to remove residual metal K and its compounds. The activated carbon is obtained after drying at 110°C; (2) adding the activated carbon obtained in step (1) to a urea aqueous solution or a melamine-ethanol solution, impregnating the mixture at room temperature, drying the mixture at 110° C., placing the mixture in a carbonization furnace, carbonizing the mixture under a nitrogen atmosphere for 1 to 3 hours, and cooling the mixture to obtain a nitrogen-containing supercapacitor carbonaceous electrode material.
2. The method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material according to claim 1, characterized in that: In step (1), the carbon-rich precursor is one or more biomass materials such as coal, petroleum coke, asphalt coke, or coconut shell.
3. The method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material according to claim 1, characterized in that: In step (1), the mass ratio of the carbon-rich precursor to the KOH powder is 1:(1-4).
4. The method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material according to claim 1, characterized in that: In step (1), the carbonization is carried out in the following order: (a) In the first heating stage, the temperature is raised from room temperature to 100-250°C at a heating rate of 5-10°C / min and kept at this temperature for 0.5-3h; (b) the second heating stage, heating from 100 to 250°C to 300 to 500°C at a heating rate of 5 to 10°C / min, and keeping the temperature for 0.5 to 3h; (c) the third heating stage, heating from 300-500°C to 700-1000°C at a heating rate of 5-10°C / min, and keeping the temperature for 0.5-3h; (d) Cooling stage: cooling to room temperature along with the furnace.
5. The method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material according to claim 1, characterized in that: In step (2), the mass ratio of urea to water in the urea aqueous solution is 1:(1-5).
6. The method for preparing a nitrogen-containing supercapacitor carbonaceous electrode material according to claim 1, characterized in that: In step (2), the mass ratio of melamine to ethanol in the melamine-ethanol solution is 1:(2-8); and the ethanol is an ethanol aqueous solution with a volume concentration of 80%.
7. The method for preparing a nitrogen-containing carbonaceous electrode material for supercapacitor according to claim 1, characterized in that: In step (2), the mass ratio of the activated carbon to the urea aqueous solution or the melamine-ethanol solution is 1:(1-10).
8. The method for preparing a nitrogen-containing carbonaceous electrode material for supercapacitor according to claim 1, characterized in that: In step (2), the immersion time is 5 to 24 hours.
9. The method for preparing a nitrogen-containing carbonaceous electrode material for supercapacitor according to claim 1, characterized in that: In step (2), the carbonization temperature is 400-1000° C., and the heating rate is 5-10° C. / min.